Lipid and glucose metabolism in white adipocytes: pathways, dysfunction and therapeutics - Morigny, Pauline; Boucher, Jeremie; Arner, Peter; Langin, Dominique (Nature reviews. Endocrinology, 2021)
In mammals, the white adipocyte is a cell type that is specialized for storage of energy (in the form of triacylglycerols) and for energy mobilization (as fatty acids). White adipocyte metabolism confers an essential role to adipose tissue in whole-body homeostasis. Dysfunction in white adipocyte metabolism is a cardinal event in the development of insulin resistance and associated disorders. This Review focuses on our current understanding of lipid and glucose metabolic pathways in the white adipocyte. We survey recent advances in humans on the importance of adipocyte hypertrophy and on the in vivo turnover of adipocytes and stored lipids. At the molecular level, the identification of novel regulators and of the interplay between metabolic pathways explains the fine-tuning between the anabolic and catabolic fates of fatty acids and glucose in different physiological states. We also examine the metabolic alterations involved in the genesis of obesity-associated metabolic disorders, lipodystrophic states, cancers and cancer-associated cachexia. New challenges include defining the heterogeneity of white adipocytes in different anatomical locations throughout the lifespan and investigating the importance of rhythmic processes. Targeting white fat metabolism offers opportunities for improved patient stratification and a wide, yet unexploited, range of therapeutic opportunities.
Keywords: bílé tukové buňky; metabolismus lipidů; Animals; homeostáza; Disease Management; Obesity; Adipocytes, White; lidé; zvířata; Lipid Metabolism; obezita; Homeostasis; management nemoci; Humans